Agile automation and unified funtional testing - Gupta Rajeev (Pearson, 2016)
Agile Automation and Unified Functional Testing is a one-stop resource that explains all concepts, features and benefits of agile automation and UFT with real-time examples and their solutions. This book starts with test automation basics and subsequently moves to its advanced concepts such as test automation life cycle, test automation approach, and framework design. It has been designed to be a beginner's guide for new users, a companion guide for experienced users, and a reference guide for professionals preparing for interviews or certification examinations on test automation and UFT.